Fermentative H2 production from food waste: Parametric analysis of factor effects. (March 2019) - Akhlaghi, M.; Boni, M.R.; Polettini, A.; Pomi, R.; Rossi, A.; De Gioannis, G.; Muntoni, A.; Spiga, D.
Highlights: A factorial study of biohydrogen production from food waste was conducted. The influence of pH and ISR on fermentation was assessed. Regression and response surface analyses were used to interpret the results. Multiple fermentation pathways were likely to overlap during fermentation. The maximum yield was 160 L H2 /kg TOCFW at pH = 5.5 and ISR = 1.74 g VS/g TOC. Abstract: Factorial fermentation experiments on food waste (FW) inoculated with activated sludge (AS) were conducted to investigate the effects of pH and the inoculum-to-substrate ratio (ISR [g VSAS /g TOCFW ]) on biohydrogen production. The two parameters affected the H2 yield, the fermentation rate and the biochemical pathways. The minimum and maximum yields were 41 L H2 /kg TOCFW (pH = 7.5, ISR = 1.74) and 156–160 L H2 /kg TOCFW (pH = 5.5, ISR = 0.58 and 1.74). The range of carbohydrates conversion into H2 was 0.37–1.45 mol H2 /mol hexose, corresponding to 9.4–36.2% of the theoretical threshold. A second-order predictive model for H2 production identified an optimum region at low pHs and high ISRs, with a theoretical maximum of 168 L H2 /kg TOCFW at pH = 5.5 and ISR = 1.74. The Spearman's correlation method revealed several relationships between the variables, suggesting the potentially governing metabolic pathways, which turned out to involve both hydrogenogenic pathways and competing reactions.